2022
DOI: 10.5296/jas.v10i3.19758
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic, Environmental, and Institutional Determinants of Cattle Ranching in the State of Pará, Brazilian Amazon

Abstract: This study investigates how socioeconomic, environmental, and institutional variables affect the growth of cattle ranching in the state of Pará, Brazilian Amazon. Covering the period from 1995 to 2019, we used an econometric model based on the Ordinary Least Squares method. Resultingly, we found that the price of fat cattle and the supply of rural credit exert a positive effect on herd growth. The deforestation rates are directly associated with herd expansion. More precisely, the variable for the deforestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In Pará, especially in the municipalities of Southeast of Pará, which are part of Brazil's high resource collection cluster, investments are mainly directed towards the acquisition, rearing, and fattening of cattle, as well as pastures, machinery, and tractors [61]. The positive effects of rural credit were also observed [20], where it was found that rural credit policies contributed to the increase in the herd in Pará from 1995 to 2019, facilitating the acquisition of animals for reproduction, investment in pasture, management, and the implementation and recovery of intensive systems.…”
Section: Determining Factors Of Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In Pará, especially in the municipalities of Southeast of Pará, which are part of Brazil's high resource collection cluster, investments are mainly directed towards the acquisition, rearing, and fattening of cattle, as well as pastures, machinery, and tractors [61]. The positive effects of rural credit were also observed [20], where it was found that rural credit policies contributed to the increase in the herd in Pará from 1995 to 2019, facilitating the acquisition of animals for reproduction, investment in pasture, management, and the implementation and recovery of intensive systems.…”
Section: Determining Factors Of Efficiencymentioning
confidence: 99%
“…Moreover, the rising consumer demand for higher quality products necessitated shorter production cycles, which rely on the nutritional value of animal feed and the herd health management. In other words, there is a need to produce more while using less land and ensuring the production of higher quality products [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the cattle herd in Pará has largely been due to the increase in pasture area, combined with animal health control, in addition to public investments, such as the availability of rural credit (Santos et al, 2012;Freitas Junior & Barros, 2021;Santos et al, 2022a), which together have generated gains in livestock productivity. The intensification of livestock activity through the proper management of pastures, the recovery of already deforested areas and the use of genetic improvement, through project financing (Rodrigues & Silva, 2016), has also led to an increase in productivity, in addition to being a way of mitigating deforestation.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%